Challenges and Strategies for English Private Tutors Throughout COVID-19 Outbreak - Mohammad Rifkon Af; Yusniawati, Maulida; Andanty, Ferra Dian (Journal of Applied Linguistics and English Education, 2024)
This study examines perceptions of e-learning methods among English tutors currently used in non-formal (online) education. This research specifically focuses on exploring the use of e-learning methods implemented during the COVID-19 pandemic in online learning. The research design uses qualitative descriptive methods. It seeks to understand perceptions of lessons using e-learning methods during the COVID-19 pandemic. Data was obtained through open interviews. Data was transcribed verbatim and analyzed descriptively. This study involved four English tutors in Surabaya as research subjects. The results of the study show that there are important considerations in the use of e-learning. Based on the results obtained by several English tutors in Surabaya, these include inadequate internet connections, limited time between tutors and students, which can cause a lack of interaction between them, and the use of masks, which can also hinder communication between students and tutors. With this strategy, tutors are smarter in finding effective solutions in developing more effective English language learning, and tutors must be able to adapt to current conditions.